Merged Volume Rendered Flat-panel Computed Tomography for Postoperative Cochlear Implant Assessment - Eisenhut, Felix; Lang, Stefan; Dörfler, Arnd; Iro, Heinrich; Hornung, Joachim; Taha, Lava (Clinical Neuroradiology, 2019)
Purpose: Evaluation of a new postprocessing method for postoperative control of cochlear implants (CI) based on a single flat detector computed tomography (FD-CT) run and volume rendering of 3D models of the inner ear. Methods: The FD-CT datasets of CIs were selected and postprocessed to generate both standard multiplanar reconstructions (MPR) and merged volume-rendered 3D datasets (MRD) of the CIs. The MRDs consisted of two different reconstructions (bone/implant) that are automatically layered to avoid manual coregistration inaccuracy. Corresponding datasets were evaluated in consensus reading in terms of qualitative (integrity, position, configuration) and quantitative (insertion depth angle) CI parameters. Results: In total 20 FD-CTs with 20 CIs were successfully postprocessed. Qualitative evaluation of MPR and MRD demonstrated complete congruency (integrity: narray integrity = 20; position: nscala tympani = 13, nscalar translocation = 7; configuration: nharmonic spiralization = 16, ntip fold over = 3, nlooped implant = 1). Adverse intracochlear implant spiralization was identified in all 10 cases with MRD and MPR. Measurement of the insertion depth angle in MRD was equivalent to that in MPR (r = 0.99; P = <0.0001). Conclusion: The use of MRD is a helpful method for precise postoperative CI assessment and provides easy detection of incorrect intracochlear spiralization.
CRIS-Team Scopus Importer:2019-09-20
Keywords: CI; FD-CT; Postprocessing; Temporal bone; Three-dimensional